PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt.L) Varietas Gendis - Hidayah, Umur; Puspitorini, Palupi; Setya, Agung (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2016)
This research have go to influence interaction between urea fertilizer and chicken manure, also best small boxist to growing and result Sweet corn (Zea mays saccharata sturt . L) gendis's variety . This research is done with to use it Group Random Planing that be arranged according to Factorial (RAKF) with 2 factor, first factor that is urea's fertilizer (U) that consist from 3 level that is urea 0 Kg/ha (U0 /control), urea 100 Kg/ha (U1), urea 200 Kg/ha (U2), urea 300 Kg/ha (U3). second Factor that is chicken manure (A) consist from 3 level that is : chicken manure 0 Kg/ha (A0 /control), chicken manure 10 Ton/ha (A1), chicken manure 20 Ton/ha (A2). Variable that to be perceived to cover high of plants, leaf number, heavy , long of tuna and tuna diameter. The data is analyzed with to use it Analisis Of Varian (ANOVA), if influency to be continued with test DMRT 5%. Research result to show that : 1). Interaction between urea's fertilizer 200 kg/ha and chicken manure 20 ton/ha give it best influence in growing and plants result sweet corn. 2 ) fertilizer Giving urea 200 kg/ha gave best influence in growing and plants result sweet corn. 3). the Giving of chicken manure 20 ton/ha give it best influence in growing and plants result sweet corn